The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12265-015-9620-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Adjuvant Therapy with Terminalia arjuna Attenuates Ongoing Inflammation and Immune Imbalance in Patients with Stable Coronary Artery Disease: In Vitro and In Vivo Evidence

Abstract: The present study evaluated the cardioprotective effects of Terminalia arjuna on classical and immuno-inflammatory markers in coronary artery disease (CAD) as an adjuvant therapy. One hundred sixteen patients with stable CAD were administered placebo/T. arjuna (500 mg twice a day) along with medications in a randomized, double-blind clinical trial. To understand the specificity and efficacy of T. arjuna, we evaluated its effect through microarray and in silico analysis in few representative samples. Data was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, an alternative system of medicine like Ayurveda advocates the use of various medicinal plants, and one such plant is Terminalia arjuna (TA), which exhibits anti-inflammatory, anti-oxidant and hypolipidemic activities [5]. Consistent with this notion, our previous clinical trial data demonstrated that T.arjuna exhibits both anti-inflammatory and anti-atherosclerotic potential in patients with stable coronary artery disease, suggesting its cardio-protective role [6]. However, there is a dearth of information on anti-atherosclerotic therapeutic effect of the extracts obtained from these natural compounds, which can be employed for treating atherosclerosis by specifically targeting macrophages and foam cells in the initial stages of the lesion development.…”
Section: Introductionmentioning
confidence: 91%
“…Therefore, an alternative system of medicine like Ayurveda advocates the use of various medicinal plants, and one such plant is Terminalia arjuna (TA), which exhibits anti-inflammatory, anti-oxidant and hypolipidemic activities [5]. Consistent with this notion, our previous clinical trial data demonstrated that T.arjuna exhibits both anti-inflammatory and anti-atherosclerotic potential in patients with stable coronary artery disease, suggesting its cardio-protective role [6]. However, there is a dearth of information on anti-atherosclerotic therapeutic effect of the extracts obtained from these natural compounds, which can be employed for treating atherosclerosis by specifically targeting macrophages and foam cells in the initial stages of the lesion development.…”
Section: Introductionmentioning
confidence: 91%
“…Wight & Arn. showed immunomodulatory effect when used as adjuvant therapy in coronary artery disease and extracts and pectins from Terminalia macroptera Guill. & Perr.…”
Section: Discussionmentioning
confidence: 99%
“…Wight & Arn. in patients with cardiovascular diseases ( Kapoor et al., 2015 ; Maulik et al., 2016 ; Priya et al., 2019 ). The report of Priya et al.…”
Section: Preclinical and Clinical Studies On Active Compounds From mentioning
confidence: 99%